SOCIODEMOGRAPHIC CHARACTERISTICS, SOCIAL MEDIA USE, POLITICAL AGENDA, FILIPINO VALUES, AND SOCIAL MEDIA INTERACTION AS DETERMINANTS OF ELECTION PARTICIPATION AMONG YOUNG ADULT FILIPINOS - Robel Abbie Narido; Denya Citadel Agustin; Kisha Carla Tan; Rowalt Alibudbud (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
The study provides information on social media participation in relation to social responsibility in voting. The results showed that sociodemographic factors have no bearing on the likelihood of democratic engagement because the elections affect all citizens of the country.  Moreover, TikTok has a positive effect on the odds of election participation among young adults. As for social media interaction, it was found that bad interactions led to lower odds of participation.  Political agendas such as agriculture, education, and law & order also led to lower odds of participation. The research utilized a survey questionnaire consisting of three sections which were sociodemographic factors, social media campaign factors, and voting behaviors of the young adult Filipino participants.